Maoism and grassroots religion: the Communist revolution and the reinvention of religious life in China - Wang, Xiaoxuan (Oxford scholarship online, 2020)
This book explores grassroots religious life under and after Mao in Rui'an County, Wenzhou, in southeastern China, a region widely known for its religious vitality. Drawing on hitherto unexplored local state archives, records of religious institutions, memoirs, and interviews, it tells the story of local communities' encounters with the Communist revolution, and their consequences, especially the competitions and struggles for religious property and ritual space. It demonstrates that, rather than being totally disrupted, religious life under Mao was characterized by remarkable variance and unevenness and was contingent on the interactions of local dynamics with Maoist campaigns-including the land reform, the Great Leap Forward, and the Cultural Revolution.